Enhancing the Efficiency and Accuracy of MLFMA-PO Hybrid Method for Analyzing Electrically Large Objects - Hao Ding; Yong Zhang; Hai Lin (International Journal of Antennas and Propagation)
An enhanced hybrid technique combining the multilevel fast multipole algorithm (MLFMA) and the physical optics (PO) is presented for analyzing scattering and radiation by electrically large structures. Based on the previously proposed hybrid technique, an extra octree structure is built for the moment method (MoM) region to accelerate the solving process and an iteration scheme is proposed to further enhance the efficiency compared to the conventional hybrid method. What is more, the modified iterative physical optics (IPO) accelerated by MLFMA technique is adopted to improve the accuracy by simulating complex structures with strong reflections. Numerical results are given to demonstrate the improved accuracy and higher accuracy of the proposed hybrid technique compared to the previous MLFMA-PO method.